Reduction of Ca2+ Entry by a Specific Block of KCa3.1 Channels Optimizes Cytotoxic Activity of NK Cells against T-ALL Jurkat Cells - Miguel Olivas-Aguirre; Laura Hadit Cruz-Aguilar; Igor Pottosin; Oxana Dobrovinskaya (Cells, 2023)
Degranulation mediated killing mechanism by NK cells is dependent on store-operated Ca2+ entry (SOCE) and has optimum at moderate intracellular Ca2+ elevations so that partial block of SOCE optimizes the killing process. In this study, we tested the effect of the selective blocker of KCa3.1 channel NS6180 on SOCE and the killing efficiency of NK cells from healthy donors and NK-92 cells against T-ALL cell line Jurkat. Patch-clamp analysis showed that only one-quarter of resting NK cells functionally express KCa3.1 current, which increases 3-fold after activation by interleukins 15 and 2. Nevertheless, blockage of KCa3.1 significantly reduced SOCE and intracellular Ca2+ rise induced by IL-15 or target cell recognition. NS6180 (1 μM) decreased NK degranulation at zero time of coculture with Jurkat cells but already after 1 h, the degranulation reached the same level as in the control. Monitoring of target cell death by flow cytometry and confocal microscopy demonstrated that NS6180 significantly improved the killing ability of NK cells after 1 h in coculture with Jurkat cells and increased the Jurkat cell fraction with apoptotic and necrotic markers. Our data evidence a strong dependence of SOCE on KCa3.1 activity in NK cells and that KCa3.1 specific block can improve NK cytotoxicity.